2019
DOI: 10.15237/gida.gd19041
|View full text |Cite
|
Sign up to set email alerts
|

Si̇yah Çay Harmaninda Parti̇kül Boyutu Ve Demleme Süresi̇ni̇n Dem Özelli̇kleri̇ Üzeri̇ne Etki̇si̇

Abstract: Satışa sunulan çaylar, genellikle farklı özellikteki çayların harmanlarıdır. Tüketici talepleri, fiyat, kalite ve volum ağırlığı gibi bazı zorunluluklar çayların harmanlanması gerektirir. Bazen farklı ülke çayları da harmanda yer alabilmektedir. Bu çalışmada, Türkiye pazarında yaygın bulunan siyah çaylardan biri 2mm, 1.4mm, 1mm, 500µm delik çaplarına sahip elek setinde partikül boyutlarına göre ayrılmış; 15, 20 ve 25 dakika süre ile geleneksel çay demleme yöntemine göre demlenmiştir. Demin bazı özellikleri üze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…The total phenolic content was also affected by particle size, and it was higher in the infusions of the ground dandelion root samples than in the unground samples ( p < .05). It was observed in another study that the total phenolic content of black tea infusion was higher when the particle size was lower (Salman et al., 2019 ). Similar findings have also been reported by other researchers (Castiglioni et al., 2015 ; Lee et al., 2014 ; Riehle et al., 2014 ).…”
Section: Resultsmentioning
confidence: 97%
“…The total phenolic content was also affected by particle size, and it was higher in the infusions of the ground dandelion root samples than in the unground samples ( p < .05). It was observed in another study that the total phenolic content of black tea infusion was higher when the particle size was lower (Salman et al., 2019 ). Similar findings have also been reported by other researchers (Castiglioni et al., 2015 ; Lee et al., 2014 ; Riehle et al., 2014 ).…”
Section: Resultsmentioning
confidence: 97%
“…Salman et al. (Ozdemir et al., 2019 ) reported that the relevant brewing time (15, 20, 25 min) had no effect on the color and brightness of the Turkish Tea group. However, we observed in our study that the brewing time resulted in changes in the color of the Turkish Tea group.…”
Section: Discussionmentioning
confidence: 99%